Locally anchoring enzymes to tissues via extracellular glycan recognition. Issue 1 (December 2018) - Farhadi, Shaheen; Bracho-Sanchez, Evelyn; Fettis, Margaret; Seroski, Dillon; Freeman, Sabrina; Restuccia, Antonietta; Keselowsky, Benjamin; Hudalla, Gregory
Abstract Success of enzymes as drugs requires that they persist within target tissues over therapeutically effective time frames. Here we report a general strategy to anchor enzymes at injection sites via fusion to galectin-3 (G3), a carbohydrate-binding protein. Fusing G3 to luciferase extended bioluminescence in subcutaneous tissue to 7 days, whereas unmodified luciferase was undetectable within hours. Engineering G3-luciferase fusions to self-assemble into a trimeric architecture extended bioluminescence in subcutaneous tissue to 14 days, and intramuscularly to 3 days. The longer local half-life of the trimeric assembly was likely due to its higher carbohydrate-binding affinity compared to the monomeric fusion. G3 fusions and trimeric assemblies lacked extracellular signaling activity of wild-type G3 and did not accumulate in blood after subcutaneous injection, suggesting low potential for deleterious off-site effects. G3-mediated anchoring to common tissue glycans is expected to be broadly applicable for improving local pharmacokinetics of various existing and emerging enzyme drugs. The use of enzymes as drugs requires that they persist within target tissues over therapeutically relevant time frames. Here the authors use a galectin-3 fusion to anchor enzymes at injection sites for up to 14 days.